Effect of Foliar Spray With Thyme Extract on Codling Moth (Cydia pomonella) Control and Some Fruit Quality of Pear (Pyrus communis L) Al-zafaraniyah selectee - Hama-salih, Fakhraddin M.; M.Raoof, Anwar; J.Rashed, Rukhosh; S.Hamid, Jalil; F.Qdir, Aras (Sulaimani Journal for Pure and Applied Sciences, 2014)
The effect of water extract of thyme significantly reduced the infestation ratio of codling moth, (Cydia pomonella) on pear fruits. The control gave the highest infestation (18.60%), while 10% thyme recorded the lowest (8.02%),. Thyme extract treatments caused significant increases with regard to the following fruit parameters : length, diameters ,fresh weight ,and volumes . as well as Total acidity%, and total soluble solids%.
Keywords: Pear; Cultivar; Alzafaraniah; Cydia pomonella; Plant extracts